PELATIHAN PEMBUATAN BRIKET DARI TONGKOL JAGUNG BAGI KELOMPOK TANI DESA MANONGKOKI, KABUPATEN TAKALAR - Rachmawaty, Rachmawaty; Pagarra, Halifah; Muis, Abd; Hiola, Siti Fatmah; YUSUF, YUSNAENI (Paramacitra Jurnal Pengabdian Masyarakat, 2024)
One of the sources of livelihood for the community in Manongkoki Village, Takalar Regency, is corn. After making observations, we found that in this area, much agricultural waste is produced, namely corn cobs. As we all know, waste is waste produced from a production process, both industrial and domestic. Moreover, until now, it is still a big problem in society. This phenomenon also occurs in the community of Manongkoki Village. The community only disposes of the corn waste, not using it at all. Seeing this phenomenon, we tried to find one solution to reduce corn cob waste by making it a product that, in addition to its beneficial value, can also later have commercial value. One way is to use the corn cobs as fuel and energy sources. The implementation methods carried out in this activity are (1) observation, (2) demonstration, and (3) direct practice by the community. The utilization of cob waste, the goal achieved is to reduce corn cob waste pollution by converting it into a valuable product, namely briquettes. Briquettes include an alternative technology as a fuel oil substitute and opening business opportunities that can increase income in Manongkoki Village.